2022
DOI: 10.1186/s40550-021-00087-w
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin detoxification of food by lactic acid bacteria

Abstract: Today, a few hundred mycotoxins have been identified and the number is rising. Mycotoxin detoxification of food and feed has been a technically uphill task for the industry. In the twenty-first century, the public demand is healthy food with minimum use of chemicals and preservatives. Among all the fungal inhibition and mycotoxin detoxification methods so far developed for food, biopreservation and biodetoxification have been found safe and reliable. Nowadays, lactic acid bacteria (LAB) are of great interest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…They are used as probiotics in several Asian fermented foods (Ngasotter et al, 2020). Some LAB are generally regarded as safe (GRAS) microorganisms (Nasrollahzadeh et al, 2022). Previous studies suggested the beneficial effects of probiotics as part of a healthy diet in addition to their health-promoting effects, such as reductions in cholesterol and immunomodulation (Ohashi and Ushida, 2009;Angmo et al, 2016).…”
mentioning
confidence: 99%
“…They are used as probiotics in several Asian fermented foods (Ngasotter et al, 2020). Some LAB are generally regarded as safe (GRAS) microorganisms (Nasrollahzadeh et al, 2022). Previous studies suggested the beneficial effects of probiotics as part of a healthy diet in addition to their health-promoting effects, such as reductions in cholesterol and immunomodulation (Ohashi and Ushida, 2009;Angmo et al, 2016).…”
mentioning
confidence: 99%
“…Typically, the mycotoxins adhere to the peptidoglycan structure of LAB cell walls, reducing their bioavailability, and consequently their toxicity since it prevents their intestinal absorption. Nonetheless, this phenomenon is strain-specific once different strains of the same species may have different bind capacities for specific mycotoxins [ 61 ]. Several LAB have been reported to be capable of binding PAT [ 15 , 62 ], OTA [ 63 ], and AFB1 [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the combination of CDPs may display cooperative antibacterial effects whether antibiotics are present or absent. As an antimicrobial activity, CDPs may prevent the synthesis of ergosterol, change the osmotic balance, make the mold membrane porous, reduce mycelial growth, and alter the nuclear DNA’s functional and structural characteristics ( Kwak et al, 2014 ; Sellamani et al, 2016 ; Nasrollahzadeh et al, 2022b ). Dal Bello et al (2007) found that cyclo(L-Phe L-Pro) and cyclo(L-Leu-L-Pro) produced by L. plantarum FST1.7 have antifungal activity against F. culmorum and F. graminearum .…”
Section: Biological Control Of Fusaria By Lactic Acid Bacteriamentioning
confidence: 99%